MOLECULAR SCREENING OF HEPATITIS B IN YOUNG ADULTS OF DISTRICT ABBOTTABAD AND MANSEHRA (Journal of Medical & Health Sciences Review, 2025)
Human hepatitis B is the inflammation of liver cells, caused by hepatitis B virus. It is a serious liver disease that occurs worldwide among people of all ages. It is a highly infectious disease and can result in severe illness, liver damage, and cirrhosis besides increasing the risk for hepatocellular carcinoma (HCC). The disease ranges in severity from a mild illness to a serious, lifelong illness. A cross sectional study was conducted during September 2017 to March 2018 to determine the frequency distribution of active hepatitis B virus (HBV) infection in apparently healthy young residents (5-24 years) of districts Abbottabad and Mansehra (KPK), Pakistan.  A total of 353 samples were collected from various schools and colleges of districts Abbottabad and Mansehra. Initially all the individuals were screened for HBV using ICT technique. ICT positive individuals were then subjected to ELISA for the detection of anti-HBV antibodies. The ELISA positive samples were then subjected to polymerase chain reaction (PCR) for further screening (detection of HBV-DNA). Out of 353 samples, 8 (2.26%) cases were found to be positive in the young population of district Mansehra, while 5 (1.41%) cases were found positive in district Abbottabad by ICT technique. By ELISA 6 (1.69%) cases were found positive in district Mansehra whereas 2 (0.56%) cases were noticed positive in district Abbottabad. Subsequent experiments, i.e., PCR showed only one case (0.699%) in district Abbottabad while 02 (0.96%) positive cases in district Mansehra. High Prevalence rate was detected both in female (2.77%) and male (2.39%) population of district Mansehra.